Wearable Glass Beads for in Vivo Dosimetry of Total Skin Electron Irradiation Treatments - Nabankema, S.K.; Jafari, S.M.; Sylvander, S.R.; Crowe, S.B. (Radiation Physics and Chemistry, 2017)
Glass beads have recently been proposed for use as radiation therapy dosimeters. Glass beads have a number of characteristics that make them suitable for in vivo skin dose measurements, including an ability to be worn on a string, and therefore avoid possible patient discomfort that may result from the use of adhesives. In this study, their use for in vivo dose measurements in total skin electron irradiation treatments has been tested. First, the dosimetric properties of cylindrical beads with a 3mm diameter were characterised using electron fields produced by a linear accelerator. The mean individual bead reproducibility was demonstrated to be within 3%; and a batch variation of 7% was observed. The beads were shown to have a linear dose response, and both dose rate and beam energy independence, within the measurement uncertainty. Phantom measurements were then performed for a total skin electron irradiation beam arrangement, and results compared against optically stimulated luminescent dosimeters at five anatomical sites. For a majority of measurement locations, agreement within 3% was observed between the two dosimetry techniques, demonstrating the feasibility of glass beads as in vivo dosimeters for total skin electron irradiation; though further investigation may be needed to minimise uncertainty in results.